Evaluasi Kualitas Layanan terhadap Operator Telekomunikasi: Tinjauan Perspektif Pelanggan - Suryat Handoko; Nilda Tri Putri; Jonrinaldi Jonrinaldi (Jurnal Optimasi Sistem Industri, 2017)
PT Semen Padang is one of the subsidiaries of PT Semen Indonesia Tbk, which is one of the state-owned enterprises engaged in the business of cement production and trade. PT Semen Padang is now actively promoting synergies and pursuing the company's performance growth to be able to cope with competition in an increasingly tight and complex cement industry. In order to face this, it is necessary to have adequate human resource management from the company. One of the successes of company’s management is the availability of sufficient human resources with high quality, have integrity, professional in accordance with the functions and tasks of each personal and work unit. Since 2015, there has been an increase in overtime hours. This is due to the shortage of employees of PT Semen Padang. The reason is the number of employees who retired and there is no recruitment. Thus, there are some tasks that have not been implemented. In addition, in May 2016 one of the KPI's timely procurement points in the spare parts field was not achieved. Therefore, it is necessary to investigate the workload of employees and give a recommendation of the optimal employee needs for this bureau in the future. The study found that Buyer Bureau Procurement of goods PT Semen Padang has only 74.4% productive work time. It is because the actual number of buyers for the spare parts field is 6 people, while the number of buyers optimal based on the calculation is 8 people.